A Lesson Learned from BSI Error Service: A Twitter Text Mining Data Approach Using NVivo - Izza, Nadia Nurul; Herindar, Evania; Akbar, Nashr (IAIN Kudus, 2024)
This research extensively examines Twitter trend data related to BSI (Bank Syariah Indonesia) error services, collecting 1,014 tweets in real-time using NCapture from NVivo 12 Plus within the timeframe of May 8-16, 2023. The key findings highlight that 81% of conversations regarding BSI error services carry a negative sentiment. Additionally, a word cloud identifies key terms such as